Preliminary Survey of Lizards of Pantai Melawi, Bachok, Kelantan, Malaysia - Mat Diah, Siti Zaleha; Hashim, Rosli; Yong, Hoi Sen; Belabut, Daicus; N., Syuhadah Dzarawi; Lim, Boo Liat (Malaysian Journal of Science, 2010)
A survey of lizards was conducted of Pantai Melawi, Bachok on 12-14 April and 11-13 May 2009. Nine species of lizards were recorded in this preliminary survey. They were from the family Agamidae (Calotes versicolor, Leiolepis belliana), family Gekkonidae (Cosymbotus platyurus, Gehyra mutilata, Gekko monarchus, Gekko gecko and Hemidactylus frenatus), family Scincidae (Eutropis multifasciata) and family Varanidae (Varanus salvator). The common species in this area were Leiolepis belliana and Hemidactylus frenatus.